The effect of tranexamic acid on the risk of death and hysterectomy in women with post-partum haemorrhage: statistical analysis plan for the WOMAN trial. Issue 1 (December 2016) - Shakur, Haleema; Roberts, Ian; Edwards, Philip; Elbourne, Diana; Alfirevic, Zarko; Ronsmans, Carine
Abstract Background Severe haemorrhage is a leading cause of maternal death worldwide. Most haemorrhage deaths occur soon after childbirth. Severe post-partum bleeding is sometimes managed by the surgical removal of the uterus (hysterectomy). Death and hysterectomy are important health consequences of post-partum haemorrhage, and clinical trials of interventions aimed at preventing these outcomes are needed. Methods The World Maternal Antifibrinolytic trial aims to determine the effect of tranexamic acid on death, hysterectomy and other health outcomes in women with post-partum haemorrhage. It is an international, multicentre, randomised trial. Approximately 20, 000 women with post-partum haemorrhage will be randomly allocated to receive an intravenous injection of either tranexamic acid or matching placebo in addition to usual care. The primary outcome measure is a composite of death in hospital or hysterectomy within 42 days of delivery. The cause of death will be described. Secondary outcomes include death, death due to bleeding, hysterectomy, thromboembolic events, blood transfusion, surgical and radiological interventions, complications, adverse events and quality of life. The health status and occurrence of thromboembolic events in breastfed babies will also be reported. We will conduct subgroup analyses for the primary outcome by time to treatment, type of delivery and cause of haemorrhage. We will conduct an analysis of treatment effect adjusted for baseline risk. Discussion The World Maternal Antifibrinolytic trial should provide reliable evidence for the efficacy of tranexamic acid in the prevention of death, hysterectomy and other outcomes that are important to patients. We present a protocol update and the statistical analysis plan for the trial. Trial registration Current Controlled TrialsISRCTN76912190 (Registration date 08 December 2008), Clinicaltrials.govNCT00872469 (Registration date 30 March 2009) and Pan African Clinical Trials Registry:PACTR201007000192283 (Registration date 02 September 2010).